El juego coletas y verdi como estrategia psicoeducativa para prevenir el abuso sexual infantil en los estudiantes de cuarto año de educación básica “a” de la unidad educativa pio Jaramillo Alvarado. 2019 – 2020 - Riofrío Peña, Karla Ivonne (2020)
Child sexual abuse is one of the forms of child maltreatment, in which the aggressor uses his power to violate the rights of the boys or girls, for this reason this thesis THE GAME COLETAS AND VERDI AS A PSYCHOEDUCATIONAL STRATEGY TO PREVENT SEXUAL CHILD ABUSE IN FOURTH YEAR STUDENTS OF BASIC EDUCATION “A” OF THE PIO JARAMILLO ALVARADO EDUCATIONAL UNIT. 2019 - 2020; aims to implement the Pigtails and Verdi Game as a psychoeducational strategy to prevent child sexual abuse, it is a descriptive, cross-sectional study and quasi-experimental design, using the methods: scientific, inductive, deductive, descriptive and synthetic analytical, the Tutty prevention knowledge and skills questionnaire, applied to the sample of 18 children aged 8 to 9 years. He found in the pretest that 55.55% of children have a medium level of knowledge about sexual abuse and 50% demonstrate a medium level of skills to identify threatening problems. After applying the Pigtails and Verdi game as a psychoeducational strategy, in the post test 77.77% of students reach a high level of knowledge and 72.22% reach a high level of prevention skills against child sexual abuse, results that were achieved through workshops which had a positive impact obtaining a correlation r = 0.71 positive mean in knowledge and r = 0.68 correlation average positive in skills against child sexual abuse. It is concluded that this proposal contributes to the sexual education of children because it increases knowledge and skills for the proposed purpose.